2006
DOI: 10.1021/la052847k
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribological Properties of Alkanephosphonic Acid Self-Assembled Monolayers on Aluminum Oxide:  Effects of Fluorination and Substrate Crystallinity

Abstract: Two phosphonic acid (PA) self-assembled monolayers (SAMs) are studied on three aluminum oxide surfaces: the C and R crystallographic planes of single crystal alpha-alumina (sapphire) and an amorphous vapor-deposited alumina thin film. SAMs are either fully hydrogenated CH3(CH2)17PO3H2 or semifluorinated CF3(CF2)7(CH2)11PO3H2. Atomic force microscope (AFM) topographic imaging reveals that the deposited films are homogeneous, atomically smooth, and stable for months in the laboratory environment. Static and adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
107
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 88 publications
18
107
0
1
Order By: Relevance
“…This model suggests that higher the adhesion, higher is the friction force. The friction of CF terminated monolayers is found to be greater [2][3][4][5][6][7][8] than that of CH terminated monolayers although the adhesion of the former is [9][10][11] less than or similar to that of the latter. As fluroalkyl and alkane are important tribological molecules, this anomaly has given rise to much debate.…”
Section: Introductionmentioning
confidence: 79%
“…This model suggests that higher the adhesion, higher is the friction force. The friction of CF terminated monolayers is found to be greater [2][3][4][5][6][7][8] than that of CH terminated monolayers although the adhesion of the former is [9][10][11] less than or similar to that of the latter. As fluroalkyl and alkane are important tribological molecules, this anomaly has given rise to much debate.…”
Section: Introductionmentioning
confidence: 79%
“…Substrates on which silane-based SAMs can form include silicon oxide, aluminum oxide, quartz, glass, mica, zinc selenide, germanium oxide, and gold [1]. Densely packed organophosphonate SAMs result from formation of highly insoluble salts between the dihydrogen phosphonate moiety and tetravalent transition metal ions [59][60][61]. Phosphonate head group can bond to the surface through both monodentate and bidentate coordinations, and the adjacent head groups are linked by inter-molecular hydrogen bonding [62].…”
Section: Adhesion Of Sams Through Different Head Groupsmentioning
confidence: 99%
“…Only when the cross-sectional diameter of the spacer chains of the SAM molecules is no larger than the distance between the anchor groups attached to the substrate can a tightly packed and well ordered monolayer form [6]. Brukman et al observed that octadecylphosphonic acid SAM had lower friction on the C crystallographic plane of single crystal R-alumina (sapphire) than on the R-plane, because the C-plane (with a repeating surface area of 0.196 nm 2 vs. 0.244 nm 2 of the R-plane) could support a denser monolayer [60]. Data from infrared absorption and X-ray photoelectron spectroscopy revealed that SAMs of alkanethiolates with poly(ethylene glycol) terminus on evaporated Au and Ag surfaces had significantly different molecular conformations, which were believed to be controlled by the lattice constants of the substrates and the ordering of the alkyl chains [67].…”
Section: Interactions Between Head Groups and Substrate Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tip can also penetrate the brush, deforming it and dissipating energy in the process. This has been termed "ploughing" [31,36,45], and experiments on self-assembled monolayers have shown that these interactions can be treated as a combination of a load-dependent term (which takes the same form as the macroscopic Amontons' law) [46] and a term reflecting the stress required to retain a sliding contact between the tip and the surface [47][48][49]. This yields where F is the lateral force on the tip, τ is a shear strength, and μ is the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%